Maxillary Cystic Ameloblastic Fibroma in an 8-Year-Old Girl: A Case Report Featuring a Rare Histological Variant - Nasser Raqe Alqhtani (Case Reports in Dentistry, 2025)
Conclusion: Clinically and radiographically, cystic ameloblastic fibroma may resemble a dentigerous cyst due to the involvement of an impacted tooth with the lesion. However, these two entities can be clearly histologically differentiated, as the distinctive odontogenic epithelial strands in a myxoid cell-rich stroma that are seen in cystic AF will be absent in a dentigerous cyst.